Associations of Irritability With Functional Connectivity of Amygdala and Nucleus Accumbens in Adolescents and Young Adults With ADHD. Issue 7 (May 2022) - Mukherjee, Prerona; Vilgis, Veronika; Rhoads, Shawn; Chahal, Rajpreet; Fassbender, Catherine; Leibenluft, Ellen; Dixon, J. Faye; Pakyurek, Murat; van den Bos, Wouter; Hinshaw, Stephen P.; Guyer, Amanda E.; Schweitzer, Julie B.
Objective: Irritability is a common characteristic in ADHD. We examined whether dysfunction in neural connections supporting threat and reward processing was related to irritability in adolescents and young adults with ADHD. Method: We used resting-state fMRI to assess connectivity of amygdala and nucleus accumbens seeds in those with ADHD ( n  = 34) and an age- and gender-matched typically-developing comparison group ( n  = 34). Results: In those with ADHD, irritability was associated with atypical functional connectivity of both seed regions. Amygdala seeds showed greater connectivity with right inferior frontal gyrus and caudate/putamen, and less connectivity with precuneus. Nucleus accumbens seeds showed altered connectivity with middle temporal gyrus and precuneus. Conclusion: The irritability-ADHD presentation is associated with atypical functional connectivity of reward and threat processing regions with cognitive control and emotion processing regions. These patterns provide novel evidence for irritability-associated neural underpinnings in adolescents and young adults with ADHD. The findings suggest cognitive and behavioral treatments that address response to reward, including omission of an expected reward and irritability, may be beneficial for ADHD.